Competencies of School Administrators in Schools Providing Expanded Educational Opportunities, under the Saraburi Primary Educational Service Area Office 1. - สมมาตร, ฉมาพร; การีเวท, สมนึก (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this study were to 1) examine the competencies of school administrators in schools providing expanded educational opportunities, 2) compare the competencies of school administrators in schools providing expanded educational opportunities, and 3) investigate guidelines for developing the competencies of school administrators in schools providing expanded educational opportunities under the Saraburi Primary Educational Service Area Office 1. The sample consisted of 162, selected using the Krejcie and Morgan sampling table and stratified random sampling. The data collection instrument was a 5-level Likert scale checklist with an Index of Content Validity (IOC) of 0.50–1.00 and a reliability coefficient of .991. Statistical analyses included frequency, percentage, mean (), standard deviation (S.D.), consistency index, reliability coefficient, t-test, and F-test using one-way ANOVA.            The research findings revealed the following: 1. A study of the core competencies of school administrators in schools providing expanded educational opportunities showed a high level. Ranked from highest to lowest mean scores, these competencies were: teamwork (= 4.22, S.D. = 0.473), self-development (= 4.15, S.D. = 0.523), achievement orientation (= 4.12, S.D. = 0.460), and good service (= 4.09, S.D. = 0.451). A study of teachers' opinions regarding the job-specific competencies of school administrators in schools providing expanded educational opportunities showed a high level. Ranked from highest to lowest mean scores, these competencies were vision (= 4.25, S.D. = 0.372), communication and motivation (= 4.23, S.D. = 0.466), analysis and synthesis (= 4.20, S.D. = 0.501), and personnel potential development (= 4.14, S.D. = 0.431). 2. A comparison of teachers' opinions on the competencies of school administrators in schools providing expanded educational opportunities under the Saraburi Primary Educational Service Area Office 1, categorized by gender and educational attainment, revealed no difference between genders, but the statistically difference was found among those with different educational attainments. A one-way analysis of variance, categorized by work experience and school size, on the core competencies and job-specific competencies of school administrators in extended education schools revealed no statistically differences. 3. The guidelines for developing the competencies of school administrators in extended education schools under the Saraburi Primary Educational Service Area Office 1, encompassing all eight competencies, had steps and processes that could be fully applied for all competencies.